Implementasi Sosialisasi Pemanfaatan Perpustakaan Digital Untuk Penguatan Literasi dan Numerasi Siswa UPTD SMAN 3 Majene - Arifin, Sartika; Anaguna, Nursyam; Aprisal, Aprisal; Yahya, Amran; Amin, Nursafitri; Hakim, Fauziah (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Technological advances have a significant impact on the transformation of libraries from traditional to digital libraries. Digital libraries are sources of educational information that provide various digital collections in the form of books, journals, articles and others including literacy and numeracy. The literacy and numeracy skills of students in Indonesia are currently still very low and students still rarely use technology as an information medium to solve mathematical problems. Therefore, the Mathematics Education Study Program of the University of West Sulawesi formed a community service team to improve literacy and numeracy through the socialization of digital libraries at the UPTD SMAN 3 Majene. The method used is socialization with three stages, namely the preparation, implementation and evaluation stages. Participants consisted of 19 students and teachers. The evaluation instrument was a questionnaire on the success and satisfaction of partners filled out by the participants. The results of filling out the questionnaire showed a level of partner satisfaction of 89.61% and the ability to apply literacy and numeracy of 96.05%. This activity has proven effective in supporting the understanding of literacy and numeracy based on digital libraries.ABSTRAKKemajuan teknologi memberikan dampak yang cukup besar bagi transformasi perpustakaan dari perpustakaan tradisional ke digital. Perpustakaan digital merupakan sumber informasi edukatif yang menyediakan berbagai koleksi digital baik berupa buku, jurnal, artikel dan lain termasuk literasi dan numerasi.  Kemampuan literasi dan numerasi siswa di Indonesia saat ini masih sangat rendah dan siswa masih sangat jarang menggunakan teknologi sebagai media informasi untuk menyelesaikan masalah matematika. Oleh karena itu Prodi Pendidikan Matematika Universitas Sulawesi Barat membentuk tim pengabdian kepada masyarakat untuk meningkatkan literasi dan numerasi melalui sosialisasi perpustakaan digital di UPTD SMAN 3 Majene. Metode yang digunakan adalah sosialisasi dengan tiga tahapan yakni tahapan persiapan, pelaksanaan dan evaluasi. Peserta terdiri dari 19 orang siswa dan guru. instrument evaluasi berupa angket keberhasilan dan kepuasan mitra yang diisi oleh peserta. Hasil dari pengisian angket menunjukkan tingkat kepuasan mitra sebesar 89,61% dan kemampuan penerapan literasi dan numerasi sebesar 96,05%. Kegiatan ini terbukti efektif dalam mendukung pemahaman literasi dan numerasi berbasis pustaka digital.